The characteristics of efficacious leader in higher education: A literature review - Ibnu Siswanto; Mingchang Wu; Hongbo Ma; Zainal Arifin; Moch Solikin; Agus Widyianto (Intelektual Pustaka Media Utama, 2023)
University is a remarkable institution which is always expected to change the world through its constantly innovative technology and science advancement and civilization promotion. Academic institution relies on its efficacious leader with vision and implementation to fully accomplish its missions. However, limited attention goes to this crucial leader’s requirements and characteristics, even faculty members in the higher education institutions studiously conduct research for external organizations. This paper presents a comprehensive analysis addressing innovative academic leader’s characteristics based on the current global situation, university mission, and unique culture. Finally, this article concluds the competencies and characteristics of efficacious academic leader demands in this changing era: envisioning the institutional future, integrating social resources with reciprocity, modeling the way with morality and integrity, executing university missions with professions and humanity, empowering team members with full support, and inspiring students with humanity. Those integrated characters could effectively guide faculty members for their future self-development, and contribute to achieving university mission on science development, producing high-quality human resources, and contributing of the human civilization promotion. This conclusion retrospectively raises further suggestions for future study, how faculty members build these characters considering the unique and complex situation of interpersonal and external factors within the university.